Even in Logic, Laws may Admit of Exceptions. A Survey of some Important Medieval Insights - Lenzen, Wolfgang (Problemos, 2024)
In this paper it is shown that many medieval logicians recognized that certain ‘laws’ hold only under certain restrictions. In particular, the basic principles of so-called connexive logic – as they had been put forward by Aristotle, Boethius, and Abelard – hold only for possible, or self-consistent, antecedents, or for non-necessary, or contingent, consequents. A similar restriction applies to the ‘law’ – possibly put forward by Chrysippus – that each proposition is compatible with itself.
Keywords: Medieval logic; Connexive logic; Aristotle’s Theses; Impossible antecedents; Necessary consequents